Felix Mendelssohn-Bartholdy - Eichens, Eduard, 1804-1877 (engraver):::Creator::::::::::::; Hildebrandt, Theodor, 1804-1874 (artist):::Contributor:::::::::::: (Germany)
Engraving of Felix Mendelssohn by Eduard Eichens based on the painting by Theodor Hildebrandt.